Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Enhancing flexural performance of rubberized concrete beams through incorporation of rice husk ash as cement replacement - Noha Hussein; Mohamed Abou Elmaaty; Mansour Alturki; Mahmoud Elsayed (Engineering Structures, 2025)

Omega-3 supplementation in migraine prophylaxis: An updated systematic review and meta-analysis - Haneen Sabet; Abdallah Abbas; Ibraheem M alkhawaldeh; Shrouk Ramadan; Moaz Elsayed Abouelmagd; Ebrahem Salah Abdul-Hamid; Ahmed Elbataa; Mona Mahmoud Elsakka; Anas Mansour; Mostafa Hossam El Din Moawad; Aynur Ozge (PharmaNutrition, 2025)

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

Effects of dietary commercial phytobiotic “Sanacore® GM” on Pacific white shrimp (Litopenaeus vannamei) growth, immune response, redux status, intestinal health, and disease resistance against Fusarium solani - El-Sayed Hemdan Eissa; Samia Elbahnaswy; Amira Hussein El-Baz; Ehab El-Haroun; Mohamed Ashour; Abdallah Tageldein Mansour; Saadea Saadony; Adel F. El-Saeed; Hoda Kabary; Samyah D. Jastaniah; Bothaina A. Alaidaroos; Manal E. Shafi; et al. (Aquaculture International, 2024)
The use of phytobiotic as functional feed additives is a promising inducer for growth performance and immune response in the Pacific whiteleg shrimp ( Litopenaeus vannamei ). It can be also commercially applied in combination with chemotherapeutic agents and vaccines. This study was carried out to evaluate the use of a commercial phytobiotic feed additive, Sanacore® GM, containing vegetable fatty acids and inactivated Saccharomyces cerevisiae with herbal extracts , on growth, body composition, non-specific immune response, antioxidant index, intestinal microflora count, and fungal resistance to Fusarium solani challenge in Pacific white shrimp, Litopenaeus vannamei . Shrimp juveniles (5.00 ± 0.1 g) were randomly distributed into 12 hapas (1 m 3 ) in triplicates at a stocking density of 20 shrimp per hapa and fed increasing levels of Sanacore® (0, 0.1, 0.2, and 0.3%) for 63 days. At the end of the feeding trial, the experimental shrimp were infected with F. solani , and mortality was recorded for 15 days. Results revealed that growth performance, feed utilization, and whole-body protein deposition were improved with increasing dietary sanacore levels. A significant improvement was reported in cellular (hemocyte counts, phagocytosis, phagocytic index, respiratory burst activity) and humoral (lysozyme and phenoloxidase) immune responses with higher dietary sanacore levels. Superoxide dismutase, catalase, and glutathione peroxidase were notably improved in shrimp-fed sanacore-supplemented diets. Meanwhile, malondialdehyde level was significantly decreased in all sanacore-supplemented shrimp. Furthermore, the dietary sanacore consistently increased probiotic bacterial counts and decreased enteric and Clostridium sp. counts in the intestine. Juveniles fed with Sanacore exhibited significantly lower mortality rates when challenged with F. solani . In conclusion, dietary sanacore could exhibit a profitable effect on the growth performance, antioxidant capacity, immunity, intestinal microbial, and the health condition of L. vannamei . Thus, sanacore can be used as an attractive feed supplement in the L. vannamei diet (0.2–0.3%), providing more insights into its application in aquaculture as a functional immunostimulant feed additive.

In vitro and in vivo antifungal and immune stimulant activities of oregano and orange peel essential oils on Fusarium solani infection in whiteleg shrimp - Abdallah Tageldein Mansour; Elsayed A. Eldessouki; Riad H. Khalil; Amany M. Diab; Talal A. M. Abo Selema; Nehal A. Younis; Nashwa Abdel-Razek (Aquaculture International, 2023)

Physiological and immunological responses of Nile tilapia fed dietary supplementation of sweet basil ethanolic and aqueous extracts - Abdallah Tageldein Mansour; Amany M. Diab; Riad H. Khalil; Elsayed A. Eldessouki; Nasser El-Sabbagh; Salma I. Elsamannoudy; Nehal A. Younis (Frontiers in Marine Science, 2023)
The use of phytotherapy in aquaculture is rapidly increasing for more environmentally sustainable measures. The present work aimed to investigate the effects of different dietary levels of sweet basil, Ocimum basilicum , leaves ethanol (BEE) or aqueous (BAE) extracts (0, 200, 300, and 500 mg/kg) on Oreochromis niloticus growth, digestive enzyme activities, hemato-biochemical profile, antioxidant status, immune responses, and resistance against Streptococcus agalactiae . Oreochromis niloticus fingerlings (40.00 ± 1.00 g/fish, n = 210) were randomly divided into seven triplicated groups (control, BEE 200 , BEE 300 , BEE 500 , BAE 200 , BAE 300 , and BAE 500 ) and fed the experimental diets for 8 weeks. The results revealed that dietary inclusion of BEE and BAE significantly improved final weight, weight gain, survival, and digestive enzyme activities. The growth response revealed a dose-dependent in favor of fish fed BEE. The hemato-biochemical biomarkers showed a significant improvement in RBCs, WBCs, hemoglobin, and lymphocyte, and a significant decrease in aminotransferases, creatinine, and cholesterol levels with dietary basil extracts. The cellular and humoral immune responses (phagocytic activity, phagocytic index, lysozyme activity, immunoglobulin) were significantly improved with increasing BEE and BAE in a dose-dependent manner. The expression of IL-1β and TNF-α genes were increased, while TGF-β was decreased in a dose-dependent manner and BEE 500 have the highest expression. The antioxidant balance was improved with increasing basil extracts supplementation, and the BEE 500 group showed the best antioxidant status. Dietary BEE and BAE increased Nile tilapia resistance to S. agalactiae . In conclusion, the dietary supplementation of both ethanolic and aqueous extracts could improve the growth performance and physiological, and immune-antioxidant status of Nile tilapia.

Soil and foliar applications of zinc sulfate and iron sulfate alleviate the destructive impacts of drought stress in wheat - Md. Abdul Mannan; Mahmuda Akter Tithi; M. Rafiqul Islam; Md. Abdullah Al Mamun; Shamim Mia; Md. Zillur Rahman; Mohamed F. Awad; Abdelaleim I. ElSayed; Elsayed Mansour; Md. Sazzad Hossain (Cereal Research Communications, 2022)

An improvement in mass flux convective parameterizations and its impact on seasonal simulations using a coupled model - Ahmed Elsayed Yousef; M. Azhar Ehsan; Mansour Almazroui; Mazen E. Assiri; Abdulrahman K. Al-Khalaf (Theoretical and Applied Climatology, 2017)

Laboratory-based surveillance of patients with bacterial meningitis in Egypt (1998–2004) - S. Afifi; M. O. Wasfy; M. A. Azab; F. G. Youssef; G. Pimentel; T. W. Graham; H. Mansour; N. Elsayed; K. Earhart; R. Hajjeh; F. Mahoney (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The Biology of Oreochromis niloticus in a Polluted Canal - Elsayed A. Khallaf; Mansour Galal; Mohammad Authman (Ecotoxicology, 2003)